Oral presentation Current challenges and opportunities in effect-based bioassays required for wastewater reuse schemes - Vasquez Christodoulou, Marlen (My University, 2026)
Vasquez MI, Current challenges and opportunities in effect-based bioassays required for wastewater reuse schemes, invited oral presentation, Young Water Professional’s Day, 10th Micropol & Ecohazard Conference of the International Water Association, Vienna, Austria, 17-20 September 2017.